Evaluation of relationship between banks lending activities and the economies in Baltic countries - Lakštutienė, Aušrinė; Barkauskaitė, Aida (Copernican Journal of Finance & Accounting, 2016)
Banks are financial institutions that are part of each country financial system. One of the banks’ core businesses is lending activity, which includes the lending activity to households, non-financial corporations and other financial institutions. Before the financial crisis until 2007 year in all the Baltic countries amounts of loans have a tendency to increase and its impact to economy become even more important. The analysis of scientific literature showed that there are different opinions concerning the relationship between banks’ lending activities (credits) and the economies. Some researchers argue that lending activities have a positive impact on country economic growth, others state that its impact is opposite – economies have a positive impact on lending activities, while the others claim that there is no relationship between mentioned variables. The performed research showed that there are strong and medium strengths positive linear relationships between lending activities and GDP in all the Baltic countries. Granger causality test showed that with one period lag, GDP affects household loans variations in Latvia and with two periods of lags, GDP has an impact on the volume of loans to non-financial corporations. While in Lithuania and Estonia the relationship, assessing one and two number of lags, between lending activities and economies was not found.